EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DAN TEAMS GAMES TOURNAMENT (TGT) PADA MATERI POKOK DIMENSI TIGA DITINJAU DARI AKTIVITAS BELAJAR SISWA SMA KELAS X DI KABUPATEN MAGETAN TAHUN PELAJARAN 2011/2012 - Prabawanti, Estu Hari (Jurnal Pembelajaran Matematika, 2013)
Abstract : The aims of this research were to know: (1) which one has a better learning achievement between cooperative learning STAD, TGT, and conventional learning, (2) which one has a better learning achievement; the students having high, medium, or low learning activity, (3) which one gives a better learning achievement based on their high, medium, and low learning activity between cooperative learning STAD, TGT and conventional learning. The population of the research was the whole students of tenth grade of senior high school in Magetan. The sampling technique was done withstratified cluster random sampling. Based on the result of data analysis, it can be concluded: (1) The cooperative learning STAD gave a better learning achievement than TGT, TGT gave a better achievement than conventional learning, and STAD gave a better learning than conventional learning. (2) The students with higher learning activity had a better learning achievement than the students with lower learning activity. (3) For studentshaving high learning activity, cooperative learning STAD had a better learning achievement than TGT and conventional learning, and cooperative learning TGT and conventional learning had the same learning achievement.For students having medium learning activity, cooperative learning STAD and TGT had the samelearning achievement and so didTGTand conventional learning, however, cooperative learning STAD had a better learning achievement than conventional learning. For students havinglow learning activity, cooperative learning STAD, TGT, and conventional learning had the same learning achievement.Keywords: Student Teams Achievement Division, Team Games Tournament,conventional , activity.